Synthetic pro‐peptide design to enhance the secretion of heterologous proteins by Saccharomyces cerevisiae - Ji Sung Cho; Hye Ji Oh; Young Eun Jang; Hyun Jin Kim; Areum Kim; Jong‐Am Song; Eun Jung Lee; Jeewon Lee (MicrobiologyOpen, 2022)
Abstract Heterologous protein production in Saccharomyces cerevisiae is a useful and effective strategy with many advantages, including the secretion of proteins that require posttranslational processing. However, heterologous proteins in S. cerevisiae are often secreted at comparatively low levels. To improve the production of the heterologous protein, human granulocyte colony‐stimulating factor (hG‐CSF) in S. cerevisiae, a secretion‐enhancing peptide cassette including an hIL‐1β‐derived pro‐peptide, was added and used as a secretion enhancer to alleviate specific bottlenecks in the yeast secretory pathway. The effects of three key parameters—N‐glycosylation, net negative charge balance, and glycine‐rich flexible linker—were investigated in batch cultures of S. cerevisiae. Using a three‐stage design involving screening, selection, and optimization, the production and secretion of hG‐CSF by S. cerevisiae were significantly increased. The amount of extracellular mature hG‐CSF produced by the optimized pro‐peptide after the final stage increased by 190% compared to that of the original pro‐peptide. Although hG‐CSF was used as the model protein in the current study, this strategy is applicable to the enhanced production of other heterologous proteins, using S. cerevisiae as the host.